Farmers' perception of Controlled Traffic Farming (CTF) and associated technologies - Maria Nygård Thomsen; Tseganesh Wubale Tamirat; Søren Marcus Pedersen; Kim Martin Lind; Hans Henrik Pedersen; Sytze de Bruin; David Nuyttens; Jurgen Vangeyte; Patrick Dermot Forristal; Claus Grøn Sørensen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
This report presents descriptive results from a recent survey conducted with the objective of assessing the use of Controlled Traffic Farming (CTF) practices and associated precision farming technologies among farmers in eight European countries. About 26 % of the surveyed farmers use some CTF systems of which 45 % apply CTF on their entire farm. For the CTF users, the major motives to use CTF are to reduce soil structure damage and to improve efficiency (reduce cost) followed by a desire to make more profit. Concern about heavy machinery – induced soil compaction and perceptions about the potentials of CTF are considerably high. However, adoption appears to be constrained mainly by: high cost of machinery modification and RTK purchase, lack of compatibility of equipment and also GPS systems from different manufacturers, and lack of decision support systems. Issues about evidence on demonstrated benefits under local conditions and availability of contractors are also mentioned as limiting factors.
Keywords: O31; O33; Q10; Q16; Q30; 330; Controlled Traffic Farming; adoption; survey; precision agriculture